A componovation perspective of innovation in emerging markets: Evidence from Indian organizations. (30th August 2019) - Dutta, Swarup K.; Snehvrat, Saurav
Abstract: In todays market landscape firms can effectively compete without the benefit of resource advantages, proprietary technology, or market power but by being more aligned towards creative combination and responsive innovation. This study approaches the concept of componovation from the composition based view (CBV) developed by Luo and Child. The CBV emphasizes how firms with ordinary resource endowments can achieve outstanding results through the creative use of open resources and unique integrating capabilities that result in an enhanced speed and a value‐price ratio that are well suited to large numbers of mass market consumers. Thus componovation is a new approach aimed at innovation in emerging markets.